Mengenal Konsep Tawakal Ibnu ‘Athaillah Al-Sakandari - Zulfian Zulfian; Happy Saputra (Program Studi Aqidah dan Filsafat Islam, 2021)
Tawaqal is one of the forms of submission of a servant to God (Allah). However, this kind of submission does not mean the absent of doing something, rather then doing something sincerely with only the hope of Allah's pleasure. This article aims to discuss the concept of submission of Ibn ‘Athaillah al-Sakandari. This study uses a qualitative method aimed at exploring the concept of Ibn ‘Athaillah al-Sakandari’s thought about tawaqqal. This study concludes that tawaqal can be achieved by focusing on the effort to enslave oneself to God as the obligations for every servant,so that Tawaqqal is regarded as a great state including physical and inner aspects of every human being. There is no reason for every one to exalt himself and look down on other servants, because the highest quality is only found in one existance, namely Allah SWT. Therefore, anyone who claims to be a servant of Allah, must surrender theirselves to Allah in all their condition. In cluding in their livelihood and other activities